Sovereignty is Superiority in the Philosophical Dimension - Yunus, Nur Rohim (BULETIN ADALAH, 2024)
This essay discusses the concept of sovereignty as the central pillar of a state's identity and superiority in the international order. Sovereignty is not just the highest power, but also the basis for a state's independence, integrity, and authority to determine its fate without external intervention. Through the perspective of thinkers such as Jean Bodin and Hans Kelsen, sovereignty is understood as the right of a state to regulate domestic affairs and maintain its integrity amidst global dynamics. Although globalisation challenges state authority, sovereignty remains a flexible and adaptive principle, allowing states to interact within equal international relations. Sovereignty also affirms the principle of non-intervention respected in international law. In the era of globalisation, despite interdependence, states must be able to maintain autonomy to protect national interests. Sovereignty symbolises the greatness and dignity of a nation that cannot be mortgaged or compromised, reflecting the right of a state to freely determine the direction of policy and maintain domestic and international stability. This essay emphasises that sovereignty must continue to be preserved, respected, and upheld to maintain the independence and identity of the nation.